2011
DOI: 10.2528/pierb10102709
|View full text |Cite
|
Sign up to set email alerts
|

Design and Simulation of Membrane Supported Transmission Lines for Interconnects in a Mm-Wave Multichip Module

Abstract: Abstract-Investigations are conducted into low-loss, low-dispersion fully shielded membrane-supported striplines designed for use in a millimeter-wave multi-chip-module. Two types of transmission line are studied: a membrane-supported shielded stripline and a novel variation of this where the membrane material is removed in areas of little mechanical importance to reduce attenuation and dispersion. The latter is possible through the exploitation of a versatile micromachining technique using SU-8 for both the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This paper describes the design, modeling and characterization of a non-contact vertical transition suitable for use in a 3D MCM employing the membrane supported transmission line interconnects developed in [1]. The results show that for an optimized 60 GHz transition, insertion losses of less than 1 dB over a 28 GHz bandwidth should be possible.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This paper describes the design, modeling and characterization of a non-contact vertical transition suitable for use in a 3D MCM employing the membrane supported transmission line interconnects developed in [1]. The results show that for an optimized 60 GHz transition, insertion losses of less than 1 dB over a 28 GHz bandwidth should be possible.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that for an optimized 60 GHz transition, insertion losses of less than 1 dB over a 28 GHz bandwidth should be possible. Further analysis has also shown that through the use of the membrane material removal technique described in [1,2] this bandwidth could be increased to around 44 GHz.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations